Floating and bioadhesive delivery system of metoprolol succinate: Formulation, development and in vitro evaluation - Rathi, Mohan; Medhekar, Rohan; Pawar, Ashish; Yewale, Chetan; Gudsoorkar, Vilas (Asian Journal of Pharmaceutics (AJP), 2014)
Aim of this study was to develop gastroretentive sustained release floating and bioadhesive drug delivery system (FBDDS) to prolong the gastric retention time of Metoprolol succinate. Tablets were prepared employing hydroxypropyl methylcellulose (HPMC K100M) as hydrophilic gel material, sodium bicarbonate as gas-generating agent and Sodium CMC (SCMC) as bioadhesive polymer. A 32 full factorial design and response surface methodology were used for designing of experiment, mapping change in responses and deriving optimum formulation. Selected independent variables were amounts HPMC K100M and SCMC polymer while floating lag time (FLT), bioadhesive strength, t50 (time taken to release 50% of drug) and t90 (time taken to release 90% of drug) were selected as dependent variables. Investigation of functionality of individual polymer to predict effect on dependent variable were statistically analyzed using the RSM.Tablets were also evaluated for physical properties, swelling and matrix erosion. Increase in concentration of HPMC and decrease in concentration of SCMC resulted in retardation of drug release. Furthermore, combination of HPMC K100M and sodium bicarbonate along with SCMC was found to affect buoyancy, bioadhesion strength and drug release. Optimized formulation showed values of dependent variables close to predicted values. Optimized formulation follows Higuchi kinetics with short buoyancy lag time, total buoyancy time of more than 24 hours and could maintain drug release for 24 hours. Content uniformity, hardness, friability, weight variation were all lying within limits. Hence, FBDDS was found to be very promising and alternative approach to increase gastric retention of dosage form and may improve bioavailability.